A systematic review of the safety and efficacy of convalescent plasma or immunoglobulin treatment for people with severe respiratory viral infections due to coronaviruses or influenza - Kimber, C; Lamikanra, AA; Geneen, LJ; Sandercock, J; Dorée, C; Valk, SJ; Estcourt, LJ (Wiley, 2022)
Objective: Evaluate the safety and effectiveness of convalescent plasma (CP) or hyperimmune immunoglobulin (hIVIG) in severe respiratory disease caused by coronaviruses or influenza, in patients of all ages requiring hospital admission. Methods: We searched multiple electronic databases for all publications to 12th October 2020, and RCTs only to 28th June 2021. Two reviewers screened, extracted, and analysed data. We used Cochrane ROB (Risk of Bias)1 for RCTs, ROBINS-I for non-RCTs, and GRADE to assess the certainty of the evidence. Results: Data from 30 RCTs and 2 non-RCTs showed no overall difference between groups for all-cause mortality and adverse events in four comparisons. Certainty of the evidence was downgraded for high ROB and imprecision. (1) CP versus standard care (SoC) (20 RCTS, 2 non-RCTs, very-low to moderate-high certainty); (2) CP versus biologically active control (6 RCTs, very-low certainty); (3) hIVIG versus SoC (3 RCTs, very-low certainty); (4) early CP versus deferred CP (1 RCT, very-low certainty). Subgrouping by titre improved precision in one outcome (30-day mortality) for the ‘COVID high-titre’ category in Comparison 1 (no difference, high certainty) and Comparison 2 (favours CP, very-low certainty). Post hoc analysis suggests a possible benefit of CP in patients testing negative for antibodies at baseline, compared with those testing positive. Conclusion: A minimum titre should be established and ensured for a positive biological response to the therapy. Further research on the impact of CP/hIVIG in patients who have not yet produced antibodies to the virus would be useful to target therapies at groups who will potentially benefit the most.